Wireless charger - Harith Iskandar, Mohd Din (2010)
Everyone nowadays is users of electrical devices such as, mobile phone, notebook, LCD, and many more. Those electrical devices supplied power by wired transmission from power supply. Wires create mess in a small room and sometimes can cause electrical shock or even house burnt due to the wire cut and short circuit. In order to prevent those things to happen, a wireless power transmission was invented. By transmitting the power through air by using radio frequency can reduce the uses of wire cable. From the power supply, a built-in coil transmits the magnetic flux as the transmitter. There is also a built in coil in the electrical devices that receive the magnetic wave and charging the electrical devices